Hybrid 2D-0D SnS2 Nanoflakes/CTS QDs-Based broadband (UV-Visible-NIR) photodetector - Yadav S.M.; Pandey A. (My University, 2025)
This article reports the SnS2 nanoflakes/(Cu2SnS3) CTS Qds-based hybrid ultrawideband photodetector (PD). The fabricated device detects the illumination in the 300-1100-nm spectrum (UV-Vis-NIR). The synergetic effect of UV detection characteristics of SnS2 nanoflakes and NIR detection characteristics of CTS Qds is utilized to obtain ultrawideband detection in the UV to NIR region. Low cost and simple solvothermal technique has been used to synthesize good quality of 2D SnS2 nanoflakes (size 146 nm) and 0D CTS Qds (size, 3.2 nm). In addition to being an active semiconductor for UV light, the SnS2 nanoflakes layer in the device has an additional task of being a carrier transport layer for the photogenerated carriers in CTS Qds. This 2D/0D (SnS2 nanoflakes/CTS Qds) PD structure fabricated on a silicon substrate has shown excellent performance in the entire range, that is, UV-Vis-NIR. The sensitivity of the fabricated CTS Qds/SnS2 nanoflake-based PD was found to be 296.2, 240.7, and 368.05 for illumination wavelengths of 320, 640, and 970 nm, respectively. The reported CTS Qds/SnS2 nanoflake-based 2D-0D hybrid detector has a responsivity of 53.88, 5.16, and 12.61 A/W for 320, 640, and 970-nm light wavelengths, respectively, and best detectivity has been observed in the order of 1013 Jones for UV light. © 1963-2012 IEEE.